Kreativitas Guru PAI dalam Mengelola Pembelajaran PAI di SMPN 29 Sijunjung - Fitri Susanti; Junaidi Junaidi; Iswantir M; Salmi Wati (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
This research raises the issue of the lack of facilities for learning media, the lack of student interaction in the learning process, and the disruption caused by students who often go in and out of class. These inadequacies can hinder the learning process and affect the teacher's creativity in managing learning. The purpose of this research is to find out how to create and maintain a maximum Islamic religious education learning atmosphere at SMPN 29 Sijunjung. The research method used is descriptive qualitative with a focus on teacher creativity in managing Islamic learning. Data were collected through observation and interviews, then analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the creativity of teachers in managing Islamic learning has been done well, but has not reached the maximum level because there are still some things that need to be improved. Factors that influence creating a maximum learning atmosphere include forgetting to convey learning objectives, interference in managing time and learning activities, lack of student involvement in learning, and limited learning media. To improve the effectiveness of learning, there needs to be more attention in managing learning in order to create an optimal learning atmosphere for students in understanding Islamic religious education.